Assessment of minnealloy fabrication via three routes - William Echtenkamp; Andrew S. Padgett; Sean R. Bishop; Philippe F. Weck; Tyra C. Douglas; C. J. Pearce; Daniel R. Lowry; Landon F. Schnebly; Jian-Ping Wang (AIP Advances)
Transformer cores exhibiting higher operating power and improved efficiency are of great interest to electrical utilities, industry, and the de-carbonization effort. Minnealloy, α″-Fe16(C,N)2, a martensite made only of iron, nitrogen, and carbon, has shown the largest saturation magnetization of any soft ferromagnet, 250 emu/g, and tunable magnetocrystalline anisotropy. Given this represents a significant increase in power transferred per cycle compared to legacy transformer core materials, we investigate three novel, industrially scalable routes for fabricating Minnealloy. The martensite phase content is investigated for each route. Vibrating sample magnetometry is used to investigate the change in saturation magnetization and coercivity with respect to the relative content of the desired phase and other iron, iron-nitride, and iron oxide phase impurities. The relationship between structure and magnetic properties of bulk α″-Fe16(C,N)2 is investigated using LDA, PBE, and PBEsol exchange-correlation functionals within the frameworks of Hubbard-corrected density functional theory (DFT+U).